Generalized relativistic harmonic oscillator in minimal length quantum mechanics - Castro, L. B.; Obispo, A. E. [UNESP] (IOP Publishing, 2017)
We solve the generalized relativistic harmonic oscillator in 1 + 1 dimensions in the presence of a minimal length. Using the momentum space representation, we explore all the possible signs of the potentials and discuss their bound-state solutions for fermions and antifermions. Furthermore, we also find an isolated solution from the Sturm-Liouville scheme. All cases already analyzed in the literature are obtained as particular cases.
Keywords: Dirac equation; generalized uncertainty principle; Relativistic oscillator